Teaching Portuguese in Northwest Mexico from a glotopolitical perspective (Research, Society and Development, 2022)
This paper describes and analyzes the history of Portuguese teaching in Baja California (Mexico), as well as the implementation of an explicit language policy at the Universidad Autónoma de Baja California (UABC) as part of an internationalization strategy conducted by a leading university in northwestern Mexico. UABC participates in students’ exchange scholarship programs such as Erasmus, CAMBRIA Group and Santander Group. It was only in 2010 that the Portuguese as a foreign language program was designed to encourage multilingualism and the internationalization of its educational programs in the international context, including Brazil and Portugal. This descriptive-analytical study analyzes, from a glotopolitical focus from Guespin, Marcellesi and Lagares. the narratives of Portuguese experts involved in the beginnings of Portuguese in the border region. With this, we seek to understand language as an essential element for society/culture and for the interaction between its speakers. The results indicate, on the one hand, the current state of teaching this foreign language and the future of the actors involved in the processes of internationalization and teaching of foreign languages in the border region (Mexico-United States). On the other hand, the results point to an eminently political process, which has produced impacts on the relations among languages in the considered space of functioning of languages.